2009
DOI: 10.1051/0004-6361/200810779
|View full text |Cite
|
Sign up to set email alerts
|

From outburst to quiescence: the decay of the transient AXP XTE J1810-197

Abstract: Aims. XTE J1810-197 is the first transient anomalous X-ray pulsar ever discovered. Its highly variable X-ray flux allowed us to study the timing and spectral emission properties of a magnetar candidate over a flux range of about two orders of magnitude. Methods. We analyzed nine XMM-Newton observations of XTE J1810-197 collected over a four year baseline (September 2003-September 2007. EPIC PN and MOS data were reduced and used for detailed timing and spectral analysis. Pulse-phase spectroscopic studies were a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
102
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(120 citation statements)
references
References 62 publications
17
102
1
Order By: Relevance
“…The portion of the emitting region on the NS surface which is in view does not vary significantly as the star rotates, resulting in a low level of modulation. Indeed the radius of the BB responsible for the magnitude of the modulation is rather high, R BB ∼ 3 km, compared for example to that measured during the outburst of another transient magnetar, XTE J1810−197, for which R bb ≤ 1 km (with kT ∼ 0.6 keV) and the PF was > ∼ 50% (Bernardini et al 2009). …”
Section: Pulsed Fractionmentioning
confidence: 79%
See 1 more Smart Citation
“…The portion of the emitting region on the NS surface which is in view does not vary significantly as the star rotates, resulting in a low level of modulation. Indeed the radius of the BB responsible for the magnitude of the modulation is rather high, R BB ∼ 3 km, compared for example to that measured during the outburst of another transient magnetar, XTE J1810−197, for which R bb ≤ 1 km (with kT ∼ 0.6 keV) and the PF was > ∼ 50% (Bernardini et al 2009). …”
Section: Pulsed Fractionmentioning
confidence: 79%
“…Ordinarily divided in two classes, there is now increasing evidence that the distinction between AXPs and SGRs originates mainly from the way in which the sources are first discovered (rather than reflect intrinsic physical differences, as also supported by recent MHD simulations, Perna & Pons 2011): AXPs, are detected by their persistent pulsed emission A&A 529, A19 (2011) magnetar from outburst to quiescence so far (Bernardini et al 2009). In the last few years, six other faint X-ray sources underwent similar outbursts (X-ray flux variation of a factor ∼100).…”
Section: Introductionmentioning
confidence: 96%
“…Most recent distance and corresponding peak luminosity estimates for this source are d = 5 kpc, L X = 1.3 × 10 36 erg s −1 (Ibrahim et al 2004), d = 3.3 kpc, L X = 5.8 × 10 35 erg s −1 (Lazaridis et al 2008), and d = 3.5 kpc, L X = 6.6 × 10 35 erg s −1 (Bernardini et al 2009). In our calculations, we take d = 3.5 kpc.…”
Section: Application Of the Model To The X-ray Enhancement Light Curvmentioning
confidence: 85%
“…We pursue the results of the work by Ertan & Erkut (2008) on the X-ray outburst light curve and the spin evolution of the transient AXP XTE J1810-197. The X-ray outburst light curve of this source showed a different decay morphology than those of persistent sources (Ibrahim et al 2004;Bernardini et al 2009). By means of model fits to the X-ray enhancement data, Ertan & Erkut (2008) concluded that this difference could be due to a viscous disk instability (see, e.g., Lasota 2001 for a review of the disk instability model (DIM)) in the fallback disks at a critical temperature in the ∼1000-2000 K range.…”
Section: Introductionmentioning
confidence: 90%
“…This so-called "j-bundle" is the result of a twist of the crust by the starquake that initiated the outburst. As the j-bundle untwists, its boundary recedes toward the magnetic pole; thus, the area of its footpoint decreases, which accounts for the declining blackbody area fitted to the X-ray spectrum (Gotthelf & Halpern 2007;Bernardini et al 2009). …”
Section: Decline Of the X-ray And Radio Luminositymentioning
confidence: 99%